Disrupting the prefrontal cortex diminishes the human ability to build a good reputation - Daniel Schunk; Ernst Fehr; Daria Knoch; Frédéric Schneider; Martin Hohmann (Verein für Socialpolitik, 2010)
Reputation formation pervades human social life. In fact, many people go to great lengths to acquire a good reputation, although building a good reputation is costly in many cases. We know little, however, about the neural underpinnings of this important social mechanism. In the present study we show that disruption of the right, but not the left, lateral prefrontal cortex (PFC) with low-frequency repetitive transcranial magnetic stimulation (rTMS) diminishes subjects' ability to build a favorable reputation. This effect occurs even though subjects' ability to behave altruistically in the absence of reputation incentives remains intact, and even though they are still able to recognize both the fairness standards necessary for acquiring and the future benefits of a good reputation. Thus, subjects with a disrupted right lateral PFC no longer seem to be able to resist the temptation to defect, even though they know that this has detrimental effects on their future reputation. This suggests an important dissociation between the knowledge about one's own best interests and the ability to act accordingly in social contexts. These results link findings on the neural underpinnings of self-control and temptation with the study of human social behavior, and they may help explain why reputation formation remains less prominent in most other species with less developed prefrontal cortices.
Keywords: D00; D83; D89; 330